Correlation between of nasopharyngeal dimensions and craniofacial structure in 8–15-year-olds: a cross-sectional study - Rosady, Chantyka; Lubis, Mimi Marina (Padjadjaran Journal of Dentistry, 2025)
Introduction: Nasopharyngeal dimensions are closely associated with craniofacial structures. Changes in the nasopharynx during facial growth may influence craniofacial development. This study aimed to analyze the correlations between nasopharyngeal dimensions and craniofacial structures in children aged 8–15 years. Methods: This study used a cross-sectional design, based on lateral cephalometry in 66 children aged 8–15 years who attended the Orthodontic Clinic, Universitas Sumatera Utara, from June-December 2022. All participants had skeletal and dental Class I relationships, no harmful habits, and were not on long-term medication. The study measured nasopharyngeal dimensions, including the mean and standard deviation of bony and soft tissue components, and craniofacial structures such as maxillary length, mandibular length, and lower anterior facial height. Data were analyzed using the Shapiro-Wilk test for normality and Pearson’s correlation test. Results: The posterior height of the nasal cavity had the highest mean value among nasopharyngeal measurements (53.99 ± 4.30 mm). Among soft tissue parameters, AD1–PNS showed the greatest mean (24.99 ± 4.70 mm) compared with PTV–AD and AD2–PNS. The mandibular length exceeded the maxillary length, and the lower anterior facial height averaged 117.74 ± 8.57 mm. Pearson’s correlation analysis showed significant correlations (p<0.05) between nasopharyngeal dimensions and craniofacial structures. The nasal floor length, posterior height of the nasal cavity, bony nasopharynx height and depth, and soft tissue measures (AD1–PNS, PTV–AD) were significantly correlated with maxillary and mandibular lengths and lower anterior facial height. Conclusion: The posterior height of the nasal cavity demonstrated the highest average value, and mandibular length was greater than maxillary length. In children aged 8–15 years, nasopharyngeal dimensions were correlated with craniofacial structures, with the exception of the nasopharyngeal depth angle and roof angle of the bony nasopharynx.